1990
DOI: 10.1007/bf01914497
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and electrical properties of dilute Cr-Ni base alloys

Abstract: The ferro-paramagnetic phase transition in dilute Cr-Ni base alloys is investigated through a qualitative study of their thermal conductivity as a function of temperature in the near vicinity of the transition. A single apparatus was used to measure the thermal and electrical conductivities and the specific heat of three thin rod samples having Cr concentrations of 0.12, 0.51 and 1.13 at. %.A voltage-temperature (V-0) realign was applied to measure the ratio between the thermal and electrical conductivities. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…5 and amounts to be 498 J kg-1 K -1 at 300 K, which is nearly close to the predetermined value [12]. In order to obtain other values of Cp at different temperatures, microfurnaces should be included at the ends of the sample.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…5 and amounts to be 498 J kg-1 K -1 at 300 K, which is nearly close to the predetermined value [12]. In order to obtain other values of Cp at different temperatures, microfurnaces should be included at the ends of the sample.…”
Section: Resultsmentioning
confidence: 94%
“…In an attempt to avoid such difficulties, measurements on ferromagnetic metals and alloys were made by an indirect method to investigate the variation of thermal conductivity with temperature in the region around the Curie temperature [2--4]. The method depends upon a relation between the temperature and the potential distributions in a current-carrying conductor kept under vacuum.In the present work, measurements were performed on dilute Ni base Cr alloy sample up to 640 K. The electrical resistivity "Q" was accurately measured [5], and it has been found that the temperature coefficient of resistivity \~ d-~j diverges logarithmically at the Curie temperature Tc. The quantity "K" can be obtained by plotting the potential difference (V) across the sample against "0.,", where "0,," is the maximum temperature attainedfor a given current in the conductor the ends of 3*…”
mentioning
confidence: 99%